Oral health conditions and self-reported presence of pain in rowers: an epidemiology study - da Silva Queiroz, R. L.; de Castro, R. K.; Caponi, L. Q.; Gosalvez, M. M.; Calvo, J. K. P.; Drago, S.; Díaz, C. C.; Fernandez, M. P. R. (2023)
Introduction: Rowers are especially prone to oral health problems due to the massive consumption of supplements and isotonic drinks that lead eating disorders, due to the need for weight control, and to the development of teeth clenching caused by the constant activation of the chewing muscles during sports activity.